2019
DOI: 10.3897/neobiota.50.34881
|View full text |Cite
|
Sign up to set email alerts
|

First indication of Japanese mitten crabs in Europe and cryptic genetic diversity of invasive Chinese mitten crabs

Abstract: The Chinese mitten crab (Eriocheir sinensis) is a prominent aquatic invader with substantial negative economic and environmental impacts. The aim of the present study was to re-evaluate the genetic diversity of mitten crabs throughout their native and invaded ranges based on publicly available sequence data, and assess if multiple introductions or rapid adaptation could be responsible for biologically divergent mitten crabs in Northern Europe. We assembled available genetic data of a fragment of the mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…Many successful invaders belong to crustaceans. Some prominent examples are the spiny-cheek crayfish Faxonius limosus (Rafinesque, 1817) and the amphipod Dikerogammarus villosus (Sowinsky, 1894) in European fresh waters (Filipová et al 2011, Rewicz et al 2015, the cladoceran Cercopagis pengoi (Ostroumov, 1891) in the North American Great Lakes (Ricciardi and MacIsaac 2000) or the Chinese mitten crab Eriocheir sinensis H. Milne Edwards, 1853 invading brackish and fresh waters globally (Dittel and Epifanio 2009;Hayer et al 2019). Numerous studies demonstrated well that such invasions may alter, more or less profoundly, the structure and functioning of aquatic ecosystems (DAISIE 2009;Ricciardi and MacIsaac 2011;Strayer 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Many successful invaders belong to crustaceans. Some prominent examples are the spiny-cheek crayfish Faxonius limosus (Rafinesque, 1817) and the amphipod Dikerogammarus villosus (Sowinsky, 1894) in European fresh waters (Filipová et al 2011, Rewicz et al 2015, the cladoceran Cercopagis pengoi (Ostroumov, 1891) in the North American Great Lakes (Ricciardi and MacIsaac 2000) or the Chinese mitten crab Eriocheir sinensis H. Milne Edwards, 1853 invading brackish and fresh waters globally (Dittel and Epifanio 2009;Hayer et al 2019). Numerous studies demonstrated well that such invasions may alter, more or less profoundly, the structure and functioning of aquatic ecosystems (DAISIE 2009;Ricciardi and MacIsaac 2011;Strayer 2012).…”
Section: Introductionmentioning
confidence: 99%
“…We trimmed, aligned and error-checked sequences in Geneious software v. 9.8.1 (Kearse et al 2012). In addition to the newly-generated COI sequences, we also included the COI data of Hänfling et al (2002) and the data accumulated by Hayer et al (2019) for northern, western and central Europe. Otto (2012) reported six additional haplotypes unique to northern Germany that were subsequently included in the study of Hayer et al (2019) as H12 to H17.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the newly-generated COI sequences, we also included the COI data of Hänfling et al (2002) and the data accumulated by Hayer et al (2019) for northern, western and central Europe. Otto (2012) reported six additional haplotypes unique to northern Germany that were subsequently included in the study of Hayer et al (2019) as H12 to H17. We recovered none of these haplotypes, neither in the samples we collected between 2018 and 2020 from the same localities nor in the museum samples that were collected by Thurid Otto herself between 2008 and 2009.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This method commonly has been used in studies on molecular species identification and the cryptic diversity of various nonnative and invasive invertebrates, including amphipods (e.g. Hayer et al, 2019; Jablonska et al, 2018; Rewicz et al, 2016; Rewicz et al, 2019; Rewicz et al, 2020). The relevant voucher information is accessible through the public data set “DS‐APOPL” (https://dx.doi.org/10.5883/DS-APOPL) in BOLD.…”
Section: Methodsmentioning
confidence: 99%